Gel network shampoo formulation and hair health benefits. (26th July 2017) - Marsh, J. M.; Brown, M. A.; Felts, T. J.; Hutton, H. D.; Vatter, M. L.; Whitaker, S.; Wireko, F. C.; Styczynski, P. B.; Li, C.; Henry, I. D.
Abstract: Objective: The objective of this work was to create a shampoo formula that contains a stable ordered gel network structure that delivers fatty alcohols inside hair. Methods: X‐ray diffraction (SAXS and WAXS), SEM and DSC have been used to confirm formation of the ordered Lβ gel network with fatty alcohol (cetyl and stearyl alcohols) and an anionic surfactant (SLE1S). Micro‐autoradiography and extraction methods using GC‐MS were used to confirm penetration of fatty alcohols into hair, and cyclic fatigue testing was used to measure hair strength. Results: In this work, evidence of a stable Lβ ordered gel network structure created from cetyl and stearyl alcohols and anionic surfactant (SLE1S) is presented, and this is confirmed via scanning electron microscopy images showing lamella layers and differential scanning calorimetry (DSC) showing new melting peaks vs the starting fatty alcohols. Hair washed for 16 repeat cycles with this shampoo showed penetration of fatty alcohols from the gel network into hair as confirmed by a differential extraction method with GC‐MS and by radiolabelling of stearyl alcohol and showing its presence inside hair cross‐sections. The gel network role in delivering fatty alcohol inside hair is demonstrated by comparing with a shampoo with added fatty alcohol not in an ordered gel network structure. The hair containing fatty alcohol was measured via the Dia‐stron cyclic fatigue instrument and showed a significantly higher number of cycles to break vs control. Conclusions: The formation of a stable gel network was confirmed in the formulated shampoo, and it was demonstrated that this gel network is important to deliver cetyl and stearyl alcohols into hair. The presence of fatty alcohol inside hair was shown to deliver a hair strength benefit via cyclic fatigue testing. Abstract : Fatty alcohol/anionic surfactant formulated in shampoo.